Ability of the sonoelastometria for deferential diagnosis of malignant and non-malignant ovarian tumors - L. A. Ashrafyan; S. V. Ivashina; N. V. Kogay; T. A. Motskobili; N. A. Babaeva; V. L. Ogryzkova (Опухоли женской репродуктивной системы)
The comparison analysis of the sonoelastomeric images with tissue density has revealed the basic laws – the greatest density of the tissues was defined in the loci painted in red color, and was in a range from 52.87 to 300 kPa. Sonoelastometric signs of malignant process presence in the ovaries have been determent at volume of the tumor not less than 15 cm3.